Ketika Indonesia Berlumur Darah dalam Jagal (The Act of Killing) - Satria Krisna Aji; Fahruddin . (GLOBAL SCIENTS PUBLISHER, 2026)
The 1965–1966 mass killings stand as one of the darkest chapters in Indonesian history, leaving deep trauma and ongoing controversies within the state’s official narrative. The documentary The Act of Killing reopens public space to examine how perpetrators represent themselves and how historical memory is constructed. This study aims to analyze the representation of the 1965–1966 violence in The Act of Killing and its impact on collective memory construction and historical justice discourse in Indonesia. This research employs a qualitative approach using film analysis as the primary method, focusing on narrative, visual, and performative elements of key scenes. In addition, a literature review of recent academic journals and historical documents was conducted to strengthen interpretation. The analysis is further supported by perspectives from memory studies and transitional justice. The findings reveal that The Act of Killing exposes the normalization of violence through the perpetrators’ perspective while simultaneously raising ethical concerns about the absence of victims’ narratives in the state’s official memory. The film serves as an alternative medium that intervenes in public and academic discourse on the 1965–1966 tragedy. The study also highlights the potential of documentary films as tools for critical history education in Indonesia. The Act of Killing significantly contributes to reopening public debate on the 1965–1966 mass killings. This study is significant as it demonstrates how visual media can serve as an instrument of collective memory and a means of reflecting on the pursuit of historical justice in Indonesia.